Ist Außenpolitik noch Außenpolitik … und was ist eigentlich Innenpolitik? Die Transformation der Politik in der „Ära des Globalismus“ - Messner, Dirk (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2000)
Globalization processes are emphatically changing the coordinate system of politics. The „epoch of the nation state“ is drawing to its end. Dirk Messner discusses four core elements involved in the change of the architecture of politics in the „era of globalism“: (1) the rapidly growing differentiation of the foreign relations of nation states as an indicator of the erosion of the classical bounds of domestic and foreign policy; (2) the trend toward the formation of a world society; (3) the growing density of transboundary networks and global problems that lead not only to an increase of international relations based on interdependency (a phenomenon long familiar to us) but to an erosion of the „internal sovereignty“ of nation states, which is turning the rules of international and global politics upside down; (4) the change of the form of political power under the conditions of globalization.